STUDY OF GUIDANCE AND COUNSELING FOR ELDERLY: A SYSTEMATIC LITERATURE REVIEW - Nur Mahardika; Uman Suherman; Agus Taufiq; Ipah Saripah (Refleksi Edukatika)
This study aims to describe the results of research on: trends and tendencies in research on guidance and counseling for the elderly.